Application of GF-2 remote sensing data for typical Quaternary stratigraphic survey in Gaizi River Basin - Zhijun Zhang; Maqiang Xu; Ming Wang; Xianju Li; Yusen Dong; Weitao Chen; Chunming Wu; Lizhe Wang (地质科技通报, 2021)
The development of domestic high resolution remote sensing satellite technology provides a new means for the investigation of macroscopic, local and detailed characteristics of the Quaternary.Alluvial-diluvial fans, valley terraces, glacial deposits are widely distributed in the eastern section of China-Pakistan Economic Corridor. In order to study the applicability of domestic high-resolution data in the Quaternary geological survey of this region, the alluvial and flood fan in front of Uruat mountain along Gaizi River basin of China-Pakistan highway and three typical Quaternary strata of Gaizi River valley terrace and Kraguirake glacial moraine were selected as the research objects in this study.Using domestic GF-2 images as the main data sources, with the aid of digital elevation model data, the remote sensing interpretation marker was established, and the fine geological interpretation was carried out.The composition and variation were found out through field verification.The previous distribution range of different periods of glacial moraines in Kailaillak was revised.Based on the analysis of the terrace in Gaizi River valley, the study area experienced at least five stages of tectonic uplift since late Epipleistocene, and the terrace base was formed by at least two stages of glaciation.This study shows that GF-2 images can not only quickly identify the change characteristics of landforms and loose deposits at macro scale, but also it can get geological phenomena that cannot be observed by conventional methods.And then it can meet the requirements of large scale interpretation and cartography.Especially in the identification of micro-geomorphology and interpretation of Quaternary strata, it can improve the level of fine geological interpretation.Research results can provide basic geological data for understanding the development and evolution process of fluvial and glaciation in the Gaizi River basin.Besides, this study can provide a typical example for remote sensing investigation of Quaternary soil mass along the China-Pakistan highway.